Effectiveness of nurse‐led counselling and education on self‐efficacy of patients with acute coronary syndrome: A randomized controlled trial - Hossein Bagheri; Sara Shakeri; Ali‐Mohammad Nazari; Shahrbanoo Goli; Mahboobeh Khajeh; Abbas Mardani; Zeljko Vlaisavljevic (Wiley, 2022)
Abstract Aim Adherence to lifestyle recommendations, medical regimens and cardiac rehabilitation is poor among patients with acute coronary syndrome. The aim of this study was to examine the effect of nurse‐led counselling and education using a person‐centred care approach on short‐term cardiac self‐efficacy in patients with acute coronary syndrome. Design A parallel, two‐armed, randomized controlled trial was conducted. Methods One hundred twenty patients who were hospitalized with diagnosis of acute coronary syndrome were selected and randomly assigned into intervention (n = 60) or control (n = 60) groups. In the intervention group, in addition to routine care, the nurse‐led counselling and education programme included two face‐to‐face sessions, two telephone counselling and education sessions, using the person‐centred care approach. Participants in the control group received only routine care. Data were collected using the cardiac self‐efficacy scale before the intervention and 1 month after discharge. Results After the intervention, we found that cardiac self‐efficacy, including the perceived self‐efficacy to control symptoms and maintain function, was statistically significantly higher in the intervention group than the control group.